OPORTUNA TOMA DE DECISIONES EN LA GESTIÓN DE CONSERVACIÓN DE LA CARRETERA - Vicente Armas, Edgar (2012)
The cycle consists of a road four phases: A) The construction which may be solid or with some flaws, upon completion of entering service. B) The slow and impairment visible, the road is experiencing wear, mainly on the paved surface and lesser degree, the rest of their structure. This occurs because of the large number of vehicles heavy and light circulating in it and shares weather and other factors,at this stage road maintenance is nil. C) Accelerated deterioration and breakdown, at the beginning of this phase, the structure basic road still intact. As this phase progresses, begins to deteriorate the basic structure, which is not visible. These damages start being punctual, and then leave finally affect spreading until most of the way, a period between two and five years. At the start of this phase should begin conserving road whose cost is 10% of the original construction. D) Total decomposition,characterized by the loss of pavement, each After passing a heavy vehicle is off pieces of asphalt layer,until finally ends being a gravel road and eventually land. The vehicles begin to experience damage in the tire axis in the chassis and dampers. In general, the operating costs vehicles up significantly and the number of accidents increases. There is a moment of need to perform certain maintenance work of a road, in the If a road with asphaltpavement. The decision making for reinforcing surfaces must be done at the beginning of phase C. But much more serious is if you pass the time to intervene timely and necessary conservation work are postponed. The delay, in the reinforcement as routine maintenance, damage occurs in the basic structure of the road. In this case, the loss is much greater, because the type of intervention needed is rehabilitation, which costs much higher than that for work done in a timely manner.